The effects of sprint interval training on performance in team sport athletes: A systematic review - Grassick, S.; O'Catháin, C.; Kelly, D.; Ward, C.; Ní Chéilleachair, N. (2020)
Sprint interval training (SIT) is a form of high intensity interval training (HIIT) in which intervals are performed in a maximal `all out` fashion for 10 to 30 seconds with 2 to 4 minutes of recovery to ensure each bout is performed maximally [1]. SIT is a practical method of sprint training often used by team sport athletes as it does not require testing prior to prescribing training [2]. Due to its time efficient nature and ability to increase aerobic capacity, SIT is becoming a popular alternative to traditional endurance training among invasion team sport athletes. Aerobic capacity is key for team sport athletes, with a higher maximal oxygen uptake seen as vital for maintaining high intensity efforts without displaying fatigue, enhancing repeated sprint ability and maintaining power outputs and distance covered during match play [3, 4]. No SLR exists that examines the effects of SIT with team sport athletes